PERAN KOMUNIKASI DALAM DIFUSI INOVASI USAHA BARANG BEKAS DI DESA PENGADANG - Haerozi (Mediakita, 2021)
Ideas that have an impact on social change must be communicated to the community. As objects, they not only know about the changes that have occurred, but they must also support and be involved so that they become part of the changes. People have always assumed that innovation always ends with the adoption of an innovation that is conveyed to them. So according to this assumption, it is as if the diffusion of innovation only focuses on spreading innovation programs or ideas to the community and only sees innovation as new ideas, ideas, methods, or products in the perspective of development communication. This study aims to find out how the innovation and development of used goods business occurred in Pengadang Village and to find out how the role of communication in the diffusion of secondhand goods business innovation occurred in Pengadang Village. This study also seeks to find out the communication of secondhand innovation in order= to develop community empowerment programs. And also its influence on the community's strategy for the development of the used goods business. This study uses a qualitative approach. Data was collected by means of observation and interview techniques, also supported by literature study. The results show that through the process of diffusion of innovation, this business has now become popular and is widely practiced by the people in Pengadang Village and with communication, the secondhand goods business in Pengadang Village is now a large growing business and is widely cultivated by the local community. The implementation of the communication strategy in the innovation of used goods processing is going well. Such as outreach activities, making pamphlets, brochures, exhibitions, and using the media to encourage the process of rapid diffusion of innovation in Pengadang Village.